"Waterloo Road". Trinidad. B.W.I. - (:unkn) unknown (W.C. Ross and Co. Ltd. Trinidad, B.W.I., 2009)
Feathery Royal palms, with large, manicured shrubs at their bases, cast shadows as they flank the road on either side in this vintage photograph taken of Waterloo Road while Trinidad was under British rule. Typically palms were planted in this manner to announce that you were about to enter a special area, estate or institution. There are buildings just behind the palms on either side of the road. A pedestrian dressed completely in white stands beside a car, possibly from the early 1900s, which is parked on the left side of the road. There are two other pedestrians just ahead of this parked car, while a similar car can be seen further down the road at the horizon.
Colour; Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Palms; Rural roads; Waterloo; Automobiles